Pedagogical mediations for non-formal nursing teaching during the COVID-19 pandemic - Juliana Amaral Prata; Alex Simões de Mello; Frances Valéria Costa e Silva; Magda Guimarães de Araujo Faria
ABSTRACT Objective: to report the experience of developing pedagogical mediations in a Virtual Learning Environment implemented in a nursing faculty during the COVID-19 pandemic. Methods: an experience report on the construction of a distance course aimed at graduates and residents of a nursing faculty at a public university located in the city of Rio de Janeiro. Results: the course's conception, operationalization and implementation were the result of a collective work that culminated in a non-formal, virtual and problematic teaching process, which reached a participation rate of 82% of enrolled students. Final considerations: even in times of social isolation, the course promoted collaborative learning of knowledge about COVID-19 and strengthened the relationship between professors and students. The possibility of carrying out distance activities based on solid methodological proposals that contradict the content logic often observed in distance learning is emphasized.